2005
DOI: 10.1208/pt060364
|View full text |Cite
|
Sign up to set email alerts
|

Proultraflexible lipid vesicles for effective transdermal delivery of levonorgestrel: Development, characterization, and performance evaluation

Abstract: The present investigation aimed at formulation, performance evaluation, and stability studies of new vesicular drug carrier system protransfersomes for transdermal delivery of the contraceptive agent, levonorgestrel. Protransfersome gel (PTG) formulations of levonorgestrel were prepared and characterized for vesicle shape, size, entrapment efficiency, turbidity, and drug permeation across rat skin and were evaluated for their stability. The system was evaluated in vivo for biological assay of progestational ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…Results of the cellular uptake study were well correlated with those reported by Cui et al The better cellular uptake of the nanoparticle formulation was further confirmed by fluorescence microscopy. Marker selected for the present study was 6-CF because it has a similar hydrophilic nature to didanosine (17). Fluorescence photomicrographs (not shown) reveal better qualitative uptake and localization of fluorescence marker loaded plain nanoparticles and mannan-coated nanoparticles in brain, spleen and lymph nodes as compared to its solution.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Results of the cellular uptake study were well correlated with those reported by Cui et al The better cellular uptake of the nanoparticle formulation was further confirmed by fluorescence microscopy. Marker selected for the present study was 6-CF because it has a similar hydrophilic nature to didanosine (17). Fluorescence photomicrographs (not shown) reveal better qualitative uptake and localization of fluorescence marker loaded plain nanoparticles and mannan-coated nanoparticles in brain, spleen and lymph nodes as compared to its solution.…”
Section: Resultsmentioning
confidence: 98%
“…Third and fourth groups received subcutaneous injection of 1.0 mL of the optimized plain nanoparticle formulation (N-C3) and mannan--coated nanoparticle formulation (N-C3-M) loaded with 6-CF (0.16%, m/V), respectively, in the dorsal part of hind paw. Rats were sacrificed after 12 h of administration and selected tissues (spleen, liver and lymph nodes) were excised, cut into small pieces and fixed using the conventional method (17). Paraffin blocks were made, 5-mm thick sections were cut using a microtome (Erma Optical Works, Japan) and examined under a fluorescence microscope (Leica, DMRBE, Germany).…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…The vesicular formulations were mixed with deionized water, in a ratio of 0.4 mL in 10 mL of deionized water, before taking the measurement using the particle size analyser in a multimodal mode. 18,23 The polydispersity index (PDI) was used as a measure of size distribution, which was measured in triplicate. A PDI value of less than 0.1 was considered as a homogeneous distribution of vesicles, whereas a PDI value of greater than 0.3 was of higher heterogeneity.…”
Section: Data Analysis and Validation Of Rsm Modelmentioning
confidence: 99%
“…liposomes, miosomes, etc. (5,6). Squamous cell carcinoma is a malignant tumor of squamous epithelium.…”
mentioning
confidence: 99%